Family Coping Strategy and Its Implication towards Quality of Life People with Mental Disabilities in Kebonjati Village, North Sumedang Sub-district, Sumedang Regency - Rini Hartini Rinda A, Azlinda Azman, Dorang Luhpuri (International Journal of Advanced Science and Technology, 2020)
Families of people with mental disabilities need to have more ability to be able to adapt and seek the best efforts in the care of family members with mental disabilities. This study aims to describe how the family coping strategy and how the quality of life of people with mental disabilities in Kebonjati Village, North Sumedang Sub-district, Sumedang Regency. This research is descriptive qualitative with data collection techniques using in-depth interviews and observation of eight research informants, namely four mothers representing families, and four people with mental disabilities. The results of the research showed that the whole family has a coping strategy, but there is a difference that one family has a good coping strategy and three families have weaknesses in building coping seen from the measurement of the coping aspects. The results also showed that families with good coping strategies lead to problem-focused coping and three weak families in developing coping strategies show emotion-focused coping, with the main characteristic being acceptance and resignation to circumstances. The results also showed that the quality of life of people with mental disabilities (PMD) in the family showed the difference of one person having a fairly good quality of life, and three people showing a low quality of life. This research concludes that family coping strategies can have a positive influence on the quality of life of people with mental disabilities. Reflections from the results of this study that families need to get support, strengthening and capacity building to build an adequate coping strategy. Keywords: Family coping strategy, people with mental disabilities, quality of life.